2017
DOI: 10.1186/s12871-017-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting urine output and 30-day mortality in goal-directed therapy: a systematic review with meta-analysis and meta-regression

Abstract: BackgroundOliguria is associated with a decreased kidney- and organ perfusion, leading to organ damage and increased mortality. While the effects of correcting oliguria on renal outcome have been investigated frequently, whether urine output is a modifiable risk factor for mortality or simply an epiphenomenon remains unclear. We investigated whether targeting urine output, defined as achieving and maintaining urine output above a predefined threshold, in hemodynamic management protocols affects 30-day mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…A recent metaanalysis including 36 randomized controlled trials in perioperative medicine and critical care demonstrated that targeting urine output does not affect 30-day mortality, suggesting that oliguria is not a modifiable risk factor for mortality. 36 On the other hand, accepting a low urine output caused by hypovolaemia including the associated haemodynamic effects might result in reduced kidney perfusion and kidney injury. The study by Mizota and colleagues in this issue of the BJA suggests that oliguria with a threshold of < 0.3 ml kg À1 h À1 might be an appropriate early intraoperative indicator of AKI.…”
Section: Perioperative Fluid Administration For Treatment Of Oliguriamentioning
confidence: 99%
“…A recent metaanalysis including 36 randomized controlled trials in perioperative medicine and critical care demonstrated that targeting urine output does not affect 30-day mortality, suggesting that oliguria is not a modifiable risk factor for mortality. 36 On the other hand, accepting a low urine output caused by hypovolaemia including the associated haemodynamic effects might result in reduced kidney perfusion and kidney injury. The study by Mizota and colleagues in this issue of the BJA suggests that oliguria with a threshold of < 0.3 ml kg À1 h À1 might be an appropriate early intraoperative indicator of AKI.…”
Section: Perioperative Fluid Administration For Treatment Of Oliguriamentioning
confidence: 99%
“…Over the years, the quality of systematic reviews conducted in the field of anaesthesia has improved, 22 and in this issue of the British Journal of Anaesthesia, Michard and colleagues 23 provide a thoroughly prepared meta-analysis of the clinical impact of perioperative goal-directed therapy when uncalibrated pulse-contour cardiac output monitors are used to titrate treatment. In line with most systematic reviews on goal-directed therapy, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Michard and colleagues 23 conclude that goal-directed therapy reduces postoperative complications. In addition, they showed that total fluid volumes were not different between experimental and control groups, although giving fluid is an intervention.…”
Section: Hedenstierna G Perchiazzi G Meyhoff Cs Larssonmentioning
confidence: 91%
“…This has been followed by a wave of systematic reviews, in particular over the last five years, trying to summarize and derive conclusions and recommendations from many of these studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Terminology for systematic reviews and meta-analyses is frequently used incorrectly. A systematic review refers to a rigorous scientific process of reviewing relevant literature whereas meta-analysis refers to a statistical method of pooling data from multiple studies to derive a summary effect estimate.…”
Section: Hedenstierna G Perchiazzi G Meyhoff Cs Larssonmentioning
confidence: 99%
“…22 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] 24 23 k 121 (10 -3 min -1 ) 236 In the whole cohort of Studies I-III, no correlation was found between preoperative dehydration as quantified by the dehydration index, and presumed preoperative hypovolemia as quantified by the volume of colloid needed during induction and the first optimisation round (Fig 15).…”
Section: Fluid Kinetics Using Non-invasive Hbmentioning
confidence: 99%